Sosialisasi Wisata Mangrove di Desa Pasar Rawa Kecamatan Gebang Kabupaten Langkat - Rahmadhani Fitri; Siti Nurhayati; Vina Arnita (Arsil Media, 2023)
Langkat Regency is one of the districts in North Sumatra Province with interesting tourist destinations to visit. This makes Langkat Regency potentially able to develop tourist attractions. One of the tourism objects that has the potential to be developed is in Pasar Rawa Village. This service activity aims to increase the knowledge of the Pasir Rawa Village community regarding the role and function of Mangroves as a tourist attraction. This beach tourism potential will attract visitors if it is planned according to the safety and comfort of visitors without damaging the ecology. The method of approach offered in community service is socialization with lectures and discussions. The results of this study increase understanding of the role and function of Mangrove forests as an attractive tourist attraction and the strategy of promoting potential village tourism can be implemented well. Where the community can understand the magnitude of coastal potential that can be used as a source of tourist objects. The high enthusiasm of the community in community service activities is a benchmark for the success of this service.